2009
DOI: 10.1901/jaba.2009.42-855
|View full text |Cite
|
Sign up to set email alerts
|

Video Modeling by Experts With Video Feedback to Enhance Gymnastics Skills

Abstract: The effects of combining video modeling by experts with video feedback were analyzed with 4 female competitive gymnasts (7 to 10 years old) in a multiple baseline design across behaviors. During the intervention, after the gymnast performed a specific gymnastics skill, she viewed a video segment showing an expert gymnast performing the same skill and then viewed a video replay of her own performance of the skill. The results showed that all gymnasts demonstrated improved performance across three gymnastics ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
130
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 13 publications
11
130
1
2
Order By: Relevance
“…A social validity measure, similar to that used by Boyer et al (2009) andFogel (2015), was used to assess the dance teacher and student reactions to the interventions. The participants were asked questions to assess the likeability and feasibility of the intervention and students were instructed to rate their answer on a five-point Likert scale (Appendix 4).…”
Section: Social Validity Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A social validity measure, similar to that used by Boyer et al (2009) andFogel (2015), was used to assess the dance teacher and student reactions to the interventions. The participants were asked questions to assess the likeability and feasibility of the intervention and students were instructed to rate their answer on a five-point Likert scale (Appendix 4).…”
Section: Social Validity Measuresmentioning
confidence: 99%
“…The instructor was asked similar questions to rate the intervention from her perspective (Appendix 5). Boyer et al (2009) andFogel (2015), the mean of the last half of baseline (last 50 % of data points) was calculated to capture any improvements that may have occurred due to dance class attendance and the mean of the last half of intervention was calculated to capture the increase that occurred over time during the intervention. Figure 1 shows the results of Cathy's performance during baseline and following the public posting intervention.…”
Section: Social Validity Measuresmentioning
confidence: 99%
“…More recently, three modeling forms have been presented: 1) self-modeling is a form of observational learning with the distinction that the observed and the observer, object, and subject, are the same person, 2) expert-modeling where the observed and the observers are not the same person and 3) model's superposition [self vs. expert model], (Boyer et al 2009;Dowrick, 2000Dowrick, , 2012. Adashevskiy, Iermakov, Korzh, Muszkieta, Krzysztof, & Cieślicka (2014), Harvey & Gittins (2014), Trout (2013), Stoicescu & Stanescu (2012), Wilson (2008), Tofan, Vlase, Teodorescu, Burca, & Candea (2006) and Durey (1995) noted that the modeling of sports skills, through simulation software and motion analysis (i.e., Human Motion Bulider, SkillSpector and Kinovea) developed athletes' knowledge and motor performance.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several studies showed a beneficial effect of video feedback in different physical activities (Atienza, Balaguer, & Garcia-Merita, 1998;Baudry, Leroy, & Chollet, 2006;Boyer, Miltenberger, Batsche, & Fogel, 2009;Clark & Ste-Marie, 2007;Eery & Morizot, 2000;Guadagnoli & Holcomb, 2002;Herbert & Landin, 1994;Hodges, Chua, & Franks, 2003;Laguna, 2000;Magill & Schoenfelder-Zohdi, 1996;Parsons & Alexander, 2012;Weir & Connor, 2009;Wulf, 2007;Wulf & Prinz, 2001), however, until now only three previous researchers have examined the athletic events. Cheraghidocheshmeh, Darush, & Mojtaba (2009) presented an important impact of educational technology on learning in exercise technical skills in amateur athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Video modeling has been used to teach a wide variety of skills (e.g., social skills, transition behaviors) to varied groups including individuals without disabilities (Boyer, Miltenberger, Batsche & Fogel, 2009), with autism spectrum disorder (Burke et al, 2013), and with developmental disorders (Laarhoven, Winiarski, Blood & Chan, 2012). Recently, video modeling has been used to teach physical skills to individuals with developmental disabilities (Buggey, 2005;D'Ateno, Mangiapanello, & Taylor, 2003;MacDonald, Clark, Garrigan & Vangala, 2005).…”
Section: Introductionmentioning
confidence: 99%